MANAJEMEN FINANSIAL DALAM KONTEKS PENDIDIKAN - Olga, Lidia; Nurraihan, Faiq (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Law No. 22 of 1999 regarding regional autonomy has had a significant impact on education management in Indonesia. Autonomy opens opportunities for educational units to manage schools independently, especially in curriculum development and funding. However, on the other hand, autonomy also poses a threat if schools are not prepared, both in terms of human resources (HR) and finance. Therefore, the success of school financial management depends heavily on the competence of the school principals. Competent school principals in school financial management are the key to ensuring that teachers and staff can deliver education with optimal quality.